نمط التعلق وعالقته بالتوافق الزواجي لدى عينة من المتزوجين بوالية االغواط - عباس حطابي; احمد شمة; عباس مريجة (My University, 2022)
تناولت هذه الدراسة موضوع نمط التعلق والتوافق الزواجي ، في شكل دراسة ل 40 حالة، بدراسة العوامل األساسية المساهمة في إرساء سيرورة التوافق الزواجي لديهم ، تم وضع فرضية تتعلق بمعرفة نوعية نمط التعلق كعامل أساسي خارجي يلعب دورا مهما في التوافق الزواجي ، ودور ه الفعال كعامل داخلي نفسي يضمن وظيفة حماية إزاء الحياة الزوجية الجيدة لتأسيس توافق ورضا نفسي لألزواج . سمح لنا المنهج الوصفي بتحليل النتائج المتحصل عليها إنطالقا من مقياس نمط التعلق و مقياس التوافق الزواجي ، أوضحت النتائج المتحصل عليها وتفسيرها إجابة عن تساؤالت الدراسة عن عالقة نمط التعلق بالتوافق الزواجي ونو عية النمط السائد لدى العينة والذي من خالله يتحقق التوافق الزواجي لدى األزواج و هذا حسب بعض المتغيرات الدخيلة كالسن ومدة الزواج والجنس، حيث كلما كان نمط التعلق آمن مرتفع وجد توافق زواجي مرتفع، خلصت الدراسة بنتيجة وجود عالقة طردية ودالة إحصائيا بين نمط التعلق والتوافق الزواجي ومن خالل ما سبق عرضه ، تم التوصل الى ان ظاهرة التعلق تعتبر شكال من أشكال مراحل تنوع الشخصية اذ تؤثر تاثيرا واضحا في التوافق الزواجي واالستقرار الزواجي بشكل عام ويمكن عرض النتائج وتلخيصها في النقاط اآلتية : 1-يرتبط أسلوب ونوع التعلق مع مظاهر التوافق الزواجي وسلوكيات الطفولة وأسلوب تكوين العالقات الرومانسية 2-يرتبط تاريخ التعلق ومستوى التوافق الزواجي والقدرة على التوافق الزواجي واالهتمام باصو ل ومبادئ تكوين االسرة 3-يلعب التعلق المتبادل دورا هاما في مستوى التوافق النفسي في حياة الكبار والراشدين 4-تؤثر أنماط التعلق على نشوء او عدم نشوء الصراع الزواجي كالطالق وغيرها 5-التعلق وأنماطه تالزم الفرد في جميع مراحل حياته العمرية This study dealt with the subject of the pattern of attachment and marital compatibility, in the form of a study of 40 cases, by examining the main factors contributing to the establishment of the process of marital adjustment for them. It guarantees a protective function towards the good marital life to establish harmony and psychological satisfaction for the spouses. The descriptive approach allowed us to analyze the results obtained from the scale of attachment style and scale of marital compatibility. The extraneous such as age, duration of marriage and gender, where the higher the secure attachment pattern, the higher marital compatibility is found. Through what was previously presented, it was concluded that the phenomenon of attachment is a form of personality diversity, as it clearly affects marital compatibility and marital stability in general. The results can be presented and summarized in the following points: 1- The style and type of attachment correlates with aspects of marital compatibility, childhood behaviors, and the method of forming romantic relationships 2- The history of attachment, the level of marital compatibility, the ability for marital compatibility, and the interest in the principles and principles of family formation are related 3- Mutual attachment plays an important role in the level of psychological adjustment in the lives of adults and adults 4- Attachment patterns affect the emergence or non-emergence of marital conflict, such as divorce and others 5- Attachment and its patterns accompany the individual in all stages of his life